Prevention of Radiodermatitis With Topical Chinese Herbal Medicine: A Systematic Review and Meta-Analysis - Hui-Bo Yu; Bao-Jin Han; Hui-Juan Cao (Frontiers Media S.A., 2022)
Objectives: Topical Chinese herbal medicine (TCHM) is widely used to prevent radiodermatitis in patients who receive radiation therapy in China. However, evidence regarding its efficacy remains limited. The purpose of the review is to evaluate the effects of TCHM in preventing radiodermatitis.Methods: The protocol of this review was registered in PROSPERO (CRD42020220620). Relevant clinical trials were identified (from January 1, 2010, to April 24, 2022) through 11 electronic databases, including PubMed, SpringerLink, Proquest, the Cochrane Central Register of Controlled Trials, Scopus, the ProQuest Dissertation & Theses Global, PsycINFO, Applied Social Sciences Index and Abstracts, the Chinese National Knowledge Infrastructure Databases, Wangfang Data Knowledge Service Platform, and the Chongqing VIP Chinese Science and Technology Periodical Database. The quality of the included trials was assessed through a risk of bias assessment using Version 2 of the Cochrane risk-of-bias tool (RoB 2.0). We included RCTs that compared TCHM single used or as adjunctive treatment with routine drugs, conventional therapy, or placebo for cancer patients who are about to start radiation therapy and do not possess any type of dermatitis or skin lesions at that time. Primary outcomes of interest were the incidence of radiodermatitis and the grade of radiodermatitis according to the RTOG (Radiation Therapy Oncology Group). Secondary outcomes included the recovery time of skin and mucosa, the occurrence time of radiodermatitis, the radiation dose, quality of life, and adverse events. Data were summarized using risk ratio (RR) calculations and 95% confidence intervals (CI) for binary outcomes or mean difference (MD) with 95% CI for continuous outcomes. Certainty of the evidence was assessed according to the GRADE criteria.Results: In this review, 38 randomized controlled trials (RCTs) were included. Risk of bias assessment through RoB 2.0 showed that two studies were rated as low risk, two studies were rated as high risk, and the rest were rated as having some concerns. Compared with routine drugs, TCHM may have an advantage in reducing RTOG grading (RR = 0.46, 95%CI 0.35-0.60), decreasing the recovery time of radiodermatitis (MD = −2.35, 95%CI 3.58 to −1.12 days), delaying the occurrence of radiodermatitis (MD = 2.36, 95%CI 1.74-2.98), and improving the quality of life of patients (RR = 1.46, 95%CI 1.03-2.06). Compared with conventional therapy, TCHM may also have an advantage in decreasing the grade of RTOG (RR = 0.28, 95%CI 0.21-0.38).Conclusion: Current low evidence revealed that TCHM may have better efficacy in the prevention of radiodermatitis; however, more high-quality RCTs are still warranted to testify this conclusion.Systematic Review Registration: (https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42020220620), identifier (PROSPERO 2020 CRD42020220620).